Upacara Tajen Pengangon Di Subak Teba Desa Adat Tangeb Kecamatan Mengwi Kabupaten Badung ( Perspektif Pendidikan Agama Hindu) - Ni Wayan Evie Armiati (Jayapangus Press, 2018)
The Tajen Pengangon ceremony in Subak Teba in the traditional village of Tangeb is unique, which is still preserved by the subak Teba village in the Tangeb village. The uniqueness of the impact of the actions and facilities used in the Tajen Pengangon Ceremony is in the form of ketupat and pillow (a type of traditional cake in Bali) which are then used to throw each other (metetimpugan) between the two groups. Facilities and infrastructures used during the ceremony are peras daksina, banten yunan, rayunan, banteng dapet pitu, banten soroan, penyeneng, tabuh, a whole bunch of chops, said peperanian. 2) This ceremony is held at the Ulun Carik Temple, the Bedugul Temple and in front of the Grand Bale and is held for 1 year at a time. 3) the series of ceremonies namely ngendangin, ngawit add, nandur, mesaba, tajen pengangon. 4) the leaders of this ceremony are stakeholders. 5) this ceremonial function, namely religious, togetherness, social and economic functions.6) the value of education contained in the values ​​of tattwa, ethics, ritual, aesthetics, togetherness and social education.